Question
upstudy study bank question image url

(a) Consider the following economic model. Where, two countries are engaged in an arms race on defense spending. We denote variable \( r \) as the annual defense expenditure for Country 1 and the variable \( s \) as the annual defense expenditure for Country 2 . We assume that each nation is ready to defend itself and has suffcient budget. We are interested in whether the defense expendituress will reach the equilibrium point(s). The interaction between the two countries expenditures is described by the following system: \[ \frac{d r}{d t}=-a r+b s+c \text {, } \] \[ \frac{d s}{d t}=m r-n s+p \text {. } \] (i) Determine the equilibrium point(s) of this system. Hint: both the r-coordinate and s-coordinate (4) should be written as a fraction with the denominator \( (a n-b m) \neq 0 \)

Ask by Pierce Kelley. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The equilibrium point is \(\left( \frac{c n + b p}{a n - b m},\ \frac{a p + c m}{a n - b m} \right)\).

Solution

To determine the equilibrium points of the given system, we set the derivatives equal to zero since, at equilibrium, the rates of change of defense expenditures \( r \) and \( s \) are zero. The system of differential equations is: \[ \frac{dr}{dt} = -a r + b s + c = 0, \] \[ \frac{ds}{dt} = m r - n s + p = 0. \] This gives us the following system of linear equations: 1. \(-a r + b s = -c\), 2. \(m r - n s = -p\). To solve for \( r \) and \( s \), we can use algebraic methods such as substitution or linear algebra (Cramer's rule). Here's how you can solve it step-by-step: 1. **Set Up the Equations:** \[ -a r + b s = -c \quad \text{(Equation 1)}, \] \[ m r - n s = -p \quad \text{(Equation 2)}. \] 2. **Use Cramer's Rule:** The coefficient matrix \( A \) and the constant vector \( \mathbf{B} \) are: \[ A = \begin{pmatrix} -a & b \\ m & -n \end{pmatrix}, \quad \mathbf{B} = \begin{pmatrix} -c \\ -p \end{pmatrix}. \] The determinant of matrix \( A \) is: \[ \text{det}(A) = (-a)(-n) - (b)(m) = a n - b m \neq 0. \] 3. **Compute \( r \) and \( s \):** Using Cramer's rule: \[ r = \frac{\begin{vmatrix} -c & b \\ -p & -n \end{vmatrix}}{\text{det}(A)} = \frac{c n + b p}{a n - b m}, \] \[ s = \frac{\begin{vmatrix} -a & -c \\ m & -p \end{vmatrix}}{\text{det}(A)} = \frac{a p + c m}{a n - b m}. \] **Therefore, the equilibrium point \((r, s)\) is:** \[ \left( \frac{c n + b p}{a n - b m},\ \frac{a p + c m}{a n - b m} \right). \] **Final Answer:** After simplifying, an equilibrium is (r, s) = ( (c n + b p)/(a n – b m), (a p + c m)/(a n – b m) ). Thus, \[ \left( \frac{c n + b p}{a n - b m},\ \frac{a p + c m}{a n - b m} \right) \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To determine the equilibrium points of the given system, we set the derivatives \(\frac{d r}{d t}\) and \(\frac{d s}{d t}\) equal to zero: 1. From the first equation: \[ 0 = -a r + b s + c \] Rearranging gives: \[ a r = b s + c \implies r = \frac{b s + c}{a} \] 2. From the second equation: \[ 0 = m r - n s + p \] Rearranging gives: \[ m r = n s - p \implies r = \frac{n s - p}{m} \] Now we have two expressions for \( r \): \[ \frac{b s + c}{a} = \frac{n s - p}{m} \] Cross-multiplying to eliminate the fractions yields: \[ m(b s + c) = a(n s - p) \] Expanding both sides: \[ mb s + mc = an s - ap \] Rearranging terms gives: \[ (mb - an)s = -mc - ap \] From this, we can solve for \( s \): \[ s = \frac{-mc - ap}{mb - an} \quad \text{(assuming } mb \neq an\text{)} \] Substituting this expression back into either equation for \( r \) (let's use the first equation): \[ r = \frac{b\left(\frac{-mc - ap}{mb - an}\right) + c}{a} \] This simplifies to: \[ r = \frac{\frac{-bmc - bap + c(mb - an)}{mb - an}}{a} = \frac{-bmc - bap + cm b - c an}{a(mb - an)} \] Breaking it further would give: \[ r = \frac{c(mb - an) - b(mc + ap)}{a(mb - an)} \] Thus the equilibrium points are given by: \[ \left( \frac{c(mb - an) - b(mc + ap)}{a(mb - an)}, \frac{-mc - ap}{mb - an} \right) \] These coordinates provide the steady-state levels of defense spending for both countries, presuming that the denominators \( (an - bm) \) and \( (a n - b m) \) are non-zero to avoid division by zero.

Related Questions

Latest Economics Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy